Pemanfaatan Digital Marketing dalam Meningkatkan Pendapatan dan Branding BUM Desa Kutukulon dan Pelaku Usaha Mikro Kecil dan Menengah (UMKM) di Kecamatan Jetis Ponorogo - Amri, Muhtadin; Ahmad Futaqi, Faruq (Sultan Journal of Social Sciences and Humanities, 2024)
This community service activity aims to provide training and assistance to Micro, Small and Medium Enterprises (MSMEs) in Jetis Ponorogo District. The service method used is the Asset-Based Community Development (ABCD) method with an Appreciative Inquiry approach. The subjects of the service included the BUM management of Mitra Puspita Kutukulon Village and MSME actors in Jetis District, Ponorogo Regency. Data was collected using primary data through interviews and questionnaires. The data analysis technique was carried out with interactive techniques. The results of this service activity show the need for the use of digital marketing to be used more widely by BUM Desa and MSME actors in order to increase their branding and income, so that the purpose of establishing BUM Desa, which is to contribute as a source of Village Original Income (PAD) can be fulfilled properly in accordance with mandate of the law. In addition, with the use of digital marketing, especially with the creation of a website as a means of promotion, it is hoped that the trust, branding and income of MSME actors can increase which in turn improves the welfare of the village community itself and revives the village economy.